2020
DOI: 10.1371/journal.pone.0234190
|View full text |Cite
|
Sign up to set email alerts
|

Positive attitudes towards feline obesity are strongly associated with ownership of obese cats

Abstract: Overweight and obesity (O&O) is a risk factor for several health conditions and can result in a shorter lifespan for cats. The objectives of this study were to investigate (a) cat owners' attitudes towards feline O&O and their associations with O&O in their cats; and (b) the risk factors for feline O&O and underweight, particularly those involving owner practice. An online survey comprising questions related to cat owners' attitudes towards feline O&O, owner-reported body weight and body condition of their cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…However, in accordance with other studies [ 4 , 60 ], our findings highlight that giving cats extra food is a risk factor for overweight. Similarly, food-begging behavior is related to overweight in cats [ 70 ]. Furthermore, from our results, most of the cats that beg for food, once it is provided by the owner, may ignore it.…”
Section: Discussionmentioning
confidence: 99%
“…However, in accordance with other studies [ 4 , 60 ], our findings highlight that giving cats extra food is a risk factor for overweight. Similarly, food-begging behavior is related to overweight in cats [ 70 ]. Furthermore, from our results, most of the cats that beg for food, once it is provided by the owner, may ignore it.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors are tested and assumed to be related with early life and rapid weight gain, this association endangers the pet to develop obesity in its adult stage (Häring et al, 2011). Teng et al (2020) found out that mixed breed cats had higher probability of developing obesity or overweight than purebred cats (Teng et al, 2020), increased prevalence of obesity in mixed breed cats has been also observed in other studies (Teng et al, 2017). German et al observed high prevalence of obesity in breeds like Beagle, Golden retriever, Pug, Cavalier King Charles spaniel and Labrador retriever and that medium sized dogs were 1.4 times more likely to develop obesity than toy breeds (German et al, 2017).…”
Section: Risk Factors For Obesity Development Breedmentioning
confidence: 99%
“…Downs et al pointed out that it is an habit among owners to feed their cats during mealtimes or when cooking food (Downes et al, 2017). Food begging behavior is common with cats that can lead to overweight (Teng et al, 2020). Sometimes the signals can be misinterpreted by the owner when the cat is vocalizing or rubbing which shows a social interaction but the owner offers it food which can lead to increase in weight (Menchetti et al, 2018).…”
Section: Dietmentioning
confidence: 99%
See 2 more Smart Citations